2017
DOI: 10.1016/j.ijid.2016.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic prescription patterns for upper respiratory tract infections in the outpatient Qatari population in the private sector

Abstract: There is a high rate of inappropriate antibiotic prescription for acute URTIs in the private health care sector in the State of Qatar. Further studies are needed to determine the population-based rates across the country. Interventions to decrease inappropriate use in such settings are urgently needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 17 publications
2
50
1
4
Order By: Relevance
“…This is especially important as there is no perceived clinical benefit from the use of antibiotics in the treatment of URTIs in many patients, including those with a common cold or persistent acute purulent rhinitis, with evidence of significant adverse events in adults from antibiotics 21,27,85,228 . Despite this lack of benefit, considerable prescribing and dispensing of antibiotics still occurs for patients with URTIs especially in LMICs 21,87,88,92,120,209,227,229,230 , although rates vary appreciably across countries. For example, Holloway et al found in their recent review that the rates of treating URTIs inappropriately in children in LMICs were high, with the use of antibiotics ranging from 42-72% of patients 97 , and Ahiabu et al found that 86.4% of patients with URTIs attending primary healthcare facilities in Ghana were prescribed an antibiotic 231 .…”
Section: Physician Management Of Urtis In Lmicsmentioning
confidence: 99%
“…This is especially important as there is no perceived clinical benefit from the use of antibiotics in the treatment of URTIs in many patients, including those with a common cold or persistent acute purulent rhinitis, with evidence of significant adverse events in adults from antibiotics 21,27,85,228 . Despite this lack of benefit, considerable prescribing and dispensing of antibiotics still occurs for patients with URTIs especially in LMICs 21,87,88,92,120,209,227,229,230 , although rates vary appreciably across countries. For example, Holloway et al found in their recent review that the rates of treating URTIs inappropriately in children in LMICs were high, with the use of antibiotics ranging from 42-72% of patients 97 , and Ahiabu et al found that 86.4% of patients with URTIs attending primary healthcare facilities in Ghana were prescribed an antibiotic 231 .…”
Section: Physician Management Of Urtis In Lmicsmentioning
confidence: 99%
“…31 between May 2014 and December 2015 for 75,733 claims for non-topical antibiotics in the private sector showed that 45% of the antibiotics were deemed inappropriate based on the accompanying diagnosis. The most common diagnosis associated with inappropriate antibiotic prescription was acute upper respiratory tract infections (28,898 claims; 85% of inappropriate prescription).…”
Section: Resultsmentioning
confidence: 99%
“…found that 45% of the patients had an inappropriate indication for antimicrobials for upper respiratory tract infection in private clinics in Qatar. 31 The reason for this is unclear, but it could be because of awareness of the emergence of antibiotic resistance or physicians being more responsive to the patient’s expectation for antimicrobials. A study in India revealed that antimicrobial prescriptions for acute, uncomplicated respiratory tract infections were common in primary care settings, less so in the public sector (45%) than in the private sector (57%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations